Retail Therapy: How a Trip to the Store Can Make You Feel Better in the Evolving Health Care Landscape Created by the Affordable Care Act - Liba, Cynthia (Journal of Law and Commerce, 2015)
As the ACA expands Medicaid eligibility by creating a national Medicaid minimum eligibility level of 133% of the federal poverty level and requires U.S. citizens to purchase health insurance as a result of the individual mandate, the shortage of primary care physicians will become painfully apparent for those seeking treatment. As a result, many health policy analysts and lawmakers are examining the potential ability of retail health clinics (RHCs) to address the consequences of primary care physician shortages in the United States, among other deficiencies in the provision of health care.